Preliminary Evidence That the Short Allele of 5-HTTLPR Moderates the Association of Psychiatric Symptom Severity on Suicide Attempt: The Example in Obsessive-Compulsive Disorder - Harika-Germaneau, Ghina; Lafay-Chebassier, Claire; Langbour, Nicolas; Thirioux, Bérangère; Wassouf, Issa; Noël, Xavier; Jaafari, Nemat; Chatard, Armand (Frontiers in Psychiatry, 2022)
Background: The severity of symptoms represents an important source of distress in patients with a psychiatric disease. However, the extent to which this endogenous stress factor interacts with genetic vulnerability factors for predicting suicide risks remains unclear. Methods: We evaluated whether the severity of symptoms interacts with a genetic vulnerability factor (the serotonin transporter gene-linked promoter region variation) in predicting the frequency of lifetime suicide attempts in patients with a psychiatric disease. Symptom severity and 5-HTTLPR polymorphism were collected from a sample of 95 patients with obsessive-compulsive disorder (OCD). Lifetime suicide attempt was the primary outcome, and antecedent of multiple suicide attempts was the secondary outcome. Results: The gene-by-symptoms interaction was associated with an excess risk of suicide attempts (OR = 4.39, 95CI[1.44, 13.38], p < 0.009) and of multiple suicide attempts (OR = 4.18, 95CI[1.04, 16.77], p = 0.043). Symptom severity (moderate, severe, or extreme) was associated with an approximately five-fold increase in the odds of a lifetime suicide attempt in patients carrying one or two copies of the short allele of 5-HTTLPR. No such relationship was found for patients carrying the long allele. Limitations: The small sample size, the restricted focus on one pathology (OCD), the retrospective nature of the suicide data, and inherent limitations of the candidate-gene approach limit the generality of the present findings. Conclusions: This study provides preliminary evidence for the gene-by-stress interaction on suicide attempt when stress is operationalized as symptom severity. Progress in suicide research may come from efforts to investigate the gene-by-symptoms interaction hypothesis in a variety of diseases.